ETHICS-BASED SOCIETY OF BUDDHISM: . - Kochumuttom, Thomas (Journal of Dharma, 1991)
What the Buddha had in mind was a new society based on dhemme. This latter term on the one hand stands for the entire body of the Buddha’s teachings, theoretical as well as practical. On the other hand, however, more frequently it refers to his practical teachings, which, of course, presuppose the theoretical ones. Among the four noble truths, which summarize. the Buddhist teachings, the first thtee (namely, the truths about suffering, its origin, and its stopping) may be considered the theoretical part; While the last one (namely the truth about the path) is the practical part. B